Isotopic Ecology and Human Diets in the Forest-Steppe Ecotone, Aisén Region, Central-Western Patagonia, Chile - Méndez, C. (2014)
This work aims to build a comprehensive isotopic ecology with the ultimate purpose of assessing long-term human diet decision-making by means of stable isotope analysis. We present a set of δ13Ccollagen and δ15Ncollagen isotopic values on the main faunal resources from the forest and steppe areas of the Aisén region (Central-Western Patagonia, Chile), in order to characterise their isotopic ranges and assess their consumption by past hunter-gatherer populations. Two sets of bioarchaeological remains are used for this comparison; a 10200-9700calyear bp assemblage from Baño Nuevo cave and a 1600-300calyear bp assemblage gathered at different locations throughout Aisén. Isotopic signals from both assemblages indicate diets based on the consumption of protein provided by terrestrial mammals from steppe environments and no long-term signature of forest-resource consumption. On the other hand, the earlier group shows values that may indicate a wider dietary breadth, although this observation is preliminary. These results further suggest that the use of forests and the resources they provided, although visible through the zooarchaeological record (i.e. taxa represented at sites), must have been discontinuous and, perhaps, marginal in comparison with steppe regions.